European football and the COVID-19 pandemic - its impact on competitions, clubs and player contracts / Chris Davies and Neil Dunbar - Davies, Chris; Dunbar, Neil (Universiti Teknologi MARA, 2022)
European football, like all major sport around the world, was heavily impacted by the COVID-19 pandemic. All national leagues in Europe had to suspend their 2019-20 seasons, though most were eventually able to complete them by extending the seasons beyond their usual finishing dates. However, these resumed fixtures had to be played in empty stadiums, as were most matches in the 2020-21 seasons. This article considers how these problems were dealt with by investigating the three key areas of competitions, the clubs and player contracts. UEFA, and the governing bodies of the various national leagues, demonstrated flexibility and adaptability in running the competitions which was crucial to their successful completion. The clubs suffered from loss of revenue due to reduced broadcasting rights and gate receipts but did obtain some financial assistance from a variety of sources. Player contracts had to be dealt with on a more individual basis depending on the law applicable to them and the negotiations between the individual clubs and their players, although there were national agreements in some countries. In the circumstances, European football appears to have survived the COVID-19 pandemic reasonably well, although the recent advent of the Omnicron variant indicates that the problems may not be over yet.